Emerging strategies to target the dysfunctional cohesin complex in cancer. (3rd June 2019) - Mintzas, Konstantinos; Heuser, Michael
ABSTRACT: Introduction : Mutations in cohesin genes have been described in numerous solid cancers and hematologic malignancies; subsequent experimental evidence has linked these mutations with carcinogenesis. Areas covered : In this review, we present current information about the physiological role of the cohesin complex in normal and malignant cells and describe current therapeutic strategies that are being explored in cohesin-mutated cancers. We discuss a range of targets and strategies that should be explored to develop targeted therapies for patients with aberrant cohesin. Expert opinion : Targeting of the cohesin complex is an underexplored area of drug development. There is a high frequency of cohesin mutations in multiple cancers, hence specific targeting strategies should be explored. Cohesins play a crucial role in cellular organization; therefore, we expect a narrow therapeutic window of direct inhibitors of cohesin components. Exploiting experimental approaches that correct dysfunctional cohesins and coupling them with current therapeutic strategies can provide novel, innovative and more effective treatment regimens. Trial registration: ClinicalTrials.gov identifier: NCT00111683. Trial registration: ClinicalTrials.gov identifier: NCT00405054. Trial registration: ClinicalTrials.gov identifier: NCT01145989. Trial registration: ClinicalTrials.gov identifier: NCT00898287. Trial registration: ClinicalTrials.gov identifier: NCT00882063.